2008
DOI: 10.1007/s00508-008-0939-z
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of supraventricular arrhythmias with regard to the type and degree of left ventricular hypertrophy in patients with hypertensive heart disease

Abstract: Concentric and eccentric types of left ventricular hypertrophy have a greater impact on the frequency of atrial arrhythmias. In the concentric type the prevalence of supraventricular premature beats correlates with the degree of left ventricular hypertrophy. Patients with moderate and severe concentric and eccentric left ventricular hypertrophy should be always tested using Holter monitoring and bicycle ergometry and treated with the maximum tolerable doses of antihypertensives, particularly with angiotensin-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The majority of our subjects were physically inactive with elevated values of lipids and urea in serum [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of our subjects were physically inactive with elevated values of lipids and urea in serum [14].…”
Section: Discussionmentioning
confidence: 99%
“…Patients were divided into three main groups with regard to LVH type: concentric (relative wall thickness [RWT] ≥ 0.45 and interventricular septum/left ventricular posterior wall [IVS/LVPW] < 1.3), eccentric (diameter LV in systoles > 32 and RWT < 0.45), and asymmetric (IVS/LVPW > 1.3), as in one previous study [13] and our earlier study [14]. RWT was measured at end-diastole as the ratio of twice the thickness of LVPW/LVIDd (left ventricular internal diastolic diameter) [15].…”
Section: Methodsmentioning
confidence: 99%
“…Atrial fibrillation associated with atrial dilatation is often observed in patients with hypertension [31]. About 40% of patients have paroxysmal atrial fibrillation or paroxysmal supraventricular tachycardia during Holter monitoring and additional 4% during the exercise test [32]. Until now it is unable to conclude whether any of the LVH types had a greater effect on the appearance of these arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…Until now it is unable to conclude whether any of the LVH types had a greater effect on the appearance of these arrhythmias. The left atrial size significantly positively correlates with left ventricular hypertrophy degree, and it seems that a larger number of supraventricular premature beats for moderate and severe concentric LVH compared to mild concentric LVH, can bee found [32]. Schannwell et al [13] also found greater prevalence of supraventricular arrhythmias proportional to the degree of LVH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation